Effect of ethnicity and rurality on treatment delays in patients with colorectal cancer in Northland, New Zealand. Issue 3 (31st August 2020) - Matthews, Christina; Walker, Michael; McLaughlin, Scott; Milloy, Michal; Harmston, Chris
Abstract: Background: Ethnic and rural disparities in medical treatment and outcomes have been demonstrated across a range of conditions, including colorectal cancer. Timely treatment and investigation of symptoms in patients with suspicion of cancer is likely to improve outcomes and patient experience. Achieving equity in timeliness of care is important in achieving the goal of equitable cancer outcomes outlined in the New Zealand cancer action plan. The aim of this study was to compare treatment times in patients with colorectal cancer, between Māori and non‐Māori patients as well as urban and rural patients in Northland, New Zealand. Methods: All adult patients diagnosed with colorectal adenocarcinoma from 2011 to 2016 were identified using hospital coding. Further information on the primary cohort was then obtained using the hospitals electronic results system, CONCERTO. The primary outcomes of interest were differences in delays to treatment between Māori and non‐Māori as well as Urban versus rural residence. Secondary outcomes of interest included rate of emergency admission and treatment by curative intent in different groups. Results: A total of 511 patients formed the primary cohort; 12% were Māori and were on average 6 years younger than non‐Māori. Māori had a 6% higher emergency admission rate and a 5% higher rate of palliative treatment intent. No significant difference in treatment delay times was seen between different ethnicities or different domiciles. Conclusion: Ethnicity and rurality were not shown to affect treatment delays. Further research in this area is needed to help attain equitable outcomes for patients with colorectal cancer in New Zealand. Abstract : Ethnic and rural disparities in medical treatment are demonstrated across many medical conditions, including colorectal cancer. This study compares investigative and treatment delays in Māori and non‐Māori as well as urban and non‐urban patients diagnosed with colorectal cancer in Northland, New Zealand. No significant difference was found between investigative and treatment delays.